Penerapan Prinsip-Prinsip WebTrust Audit dalam Sistem Informasi Akuntansi dengan Elektronik Banking berdasarkan Technology Acceptance Model (Studi kasus pada Bank Syariah Indonesia Branch Office Lingkup Kota Semarang) - Dimas Daffa Saputra; Endang Kiswara (Diponegoro Journal of Accounting, 2022)
This research aims to estimate the predictions regarding the effect of the application of the WebTrust Audit principle in the Accounting Information System which is implemented through electronic banking acceptance. This research is the development of the Technology Acceptance Model (TAM) theory found by Davis (1989) by adding external factors, namely the principles of WebTrust Audit. Overall there are 150 samples of Bank Syariah Indonesia customers used in this study. The data analysis method used is Partial Least Squares with the SmartPLS 3.3.9 statistical program.The results of this study indicate that the Processing Integrity Principle is the most influential factor in influencing electronic banking users. Overall, the application of the WebTrust Audit principle can be used as an external factor that can affect electronic banking users.The findings of this study recommend Bank Syariah Indonesia to be able to improve the application of the principles of WebTrust Audit in order to increase the use of electronic banking and evaluate multiple security in Mobile Banking to increase the perceived usefulness of Mobile Banking by users.